2013
DOI: 10.1103/physreva.87.062122
|View full text |Cite
|
Sign up to set email alerts
|

Experimental adaptive Bayesian tomography

Abstract: We report an experimental realization of an adaptive quantum state tomography protocol. Our method takes advantage of a Bayesian approach to statistical inference and is naturally tailored for adaptive strategies. For pure states we observe close to 1/N scaling of infidelity with overall number of registered events, while best non-adaptive protocols allow for 1/ √ N scaling only. Experiments are performed for polarization qubits, but the approach is readily adapted to any dimension.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 20 publications
2
83
0
Order By: Relevance
“…The latter ideas were implemented experimentally for a single parameter estimation [6,7]. Two recent experimental implementations [8,9] have demonstrated the quadratic enhancement in the accuracy of reconstruction, measured as the infidelity with the "true" state, for adaptive estimation of qubit states. The experiment in [8] relied on a single adaptive step: when half of the data are collected, the most likely state is estimated and the following measurements are performed in the eigenbasis of the estimated state.…”
Section: Introductionmentioning
confidence: 99%
“…The latter ideas were implemented experimentally for a single parameter estimation [6,7]. Two recent experimental implementations [8,9] have demonstrated the quadratic enhancement in the accuracy of reconstruction, measured as the infidelity with the "true" state, for adaptive estimation of qubit states. The experiment in [8] relied on a single adaptive step: when half of the data are collected, the most likely state is estimated and the following measurements are performed in the eigenbasis of the estimated state.…”
Section: Introductionmentioning
confidence: 99%
“…We analyze the applicability of different sets of probe states for data-pattern tomography. For the chosen basis set, the efficiency of the reconstruction could be enhanced using, for example, the adaptive Bayesian procedure [19][20][21][22].…”
Section: Optimal Basis Setsmentioning
confidence: 99%
“…The papers [12,5] compare Bayesian methods to other methods on simulated data. More recently, [30,19,31,38] discuss efficient algorithms for computing Bayesian estimators. Importantly, [9] showed that Bayesian method comes with natural error bars and is the most accurate scheme w.r.t.…”
Section: Introductionmentioning
confidence: 99%